INTEGRATION OF ROMANIAN AGRO-FOOD SYSTEM INTO EUROPEAN UNION - Irina Elena, Petrescu (Economics of Agriculture, 2012)
Romanian accessing to European Union does not automatically represent its integration. The integration of agro food system in the European Union involves a series of issues, first should agricultural economy integrate into the national economy and second, the agro food sector should integrate into the EU structures. After 4 years of accessing to EU, Romanian agriculture still faces a series of problems, mainly regarding the average yields per hectare. In the paper it is presented a comparative analysis regarding the cereal production for Romania vs. France and the main conclusion is even if the Romanian cereal producers has half of the cost of the France producers, he still receives 3 times less of the price per hectare.